Optimization of protein requirements and feed restriction in Penaeus vannamei (Boone, 1931) biofloc culture - S. Ferrando-Juan; J. Gómez-Aguilera; S. Martínez-Llorens; A. Tomás-Vidal; M. Rodilla; M. Jover-Cerdá; F. J. Moyano; D. S. Peñaranda (Aquaculture International, 2026)

Evidence for protracted fluid mobility from 40Ar/39Ar stepwise crushing of quartz-rich veins and high-grade rocks - Intan Chalid; Jan R. Wijbrans; Yang Wu; Simona Ferrando; Sander Hoogendoorn; Leo M. Kriegsman; Klaudia F. Kuiper (Geochimica et Cosmochimica Acta, 2025)

Seed banking of mediterranean coastal plants: an analysis to identify current seed availability and gaps to guide future seed collection and habitat restoration activities - Marcello De Vitis; Valter Di Cecco; Mohamed Abdelaal; Gianluigi Bacchetta; Jože Bavcon; Kenza Saadiya Benmenni; Maurizio Bianchelli; Magda Bou Dagher Kharrat; Joseph A. Buhagiar; Francesca Carruggio; Angelino Carta; Simona Casavecchia; et al. (Journal of Coastal Conservation, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Update on the status of the contamination by organotin compounds in sediment of Nuevo Gulf, Argentina. Insights from field and experimental studies - N.A. Gomez; J. Sturla Lompré; A. Ferrando; M. Garrido; C.E. Domini (Marine Pollution Bulletin, 2024)

Deep segregation and crystallization of ultra-depleted melts in the sub-ridge mantle - C. Ferrando; G. Borghini; C. Sani; F. Genske; M. Ligi; A. Stracke; A. Sanfilippo (Chemical Geology, 2024)

Linking processing to formulation in dynamic membranes of tunable pore size for lemon oil emulsions - W. Kaade; M. Ferrando; S. de Lamo-Castellví; C. Güell (Journal of Food Engineering, 2023)

Differential response of denitrifying and diazotrophic soil populations to short and long-term exposure of glyphosate and atrazine - L. Ferrando; M. I. Bellini; A. Fernández-Scavino (Environmental Sustainability, 2023)

Fields with no recent legume cultivation have sufficient nitrogen-fixing rhizobia for crops of faba bean (Vicia faba L.) - Marta Maluk; Francesc Ferrando-Molina; Laura Lopez del Egido; Adrian Langarica-Fuentes; Genet Gebre Yohannes; Mark W. Young; Peter Martin; Richard Gantlett; Greg Kenicer; Cathy Hawes; Graham S. Begg; Richard S. Quilliam; et al. (Plant and Soil, 2022)
Purpose (1) To assess the biological N fixation (BNF) potential of varieties of faba bean ( Vicia faba L.) cropped with or without compost in an experimental field-scale rotation with no recent history of legumes, (2) to enumerate soil populations of Rhizobium leguminosarum sv. viciae ( Rlv ), and to genetically characterize the nodulating Rlv strains, (3) compare BNF with other sites in Britain. Methods BNF was evaluated from 2012 to 2015 using 15 N natural abundance. Treatments were either PK fertilizer or compost. Soil rhizobial populations were determined using qPCR, the symbiotic rhizobia genotyped (16 S rRNA, nodA and nodD genes), and their BNF capacity assessed ex situ . The reliance of legumes on BNF at other British sites was estimated in a single season, and their nodulating symbionts examined. Results Faba bean obtained most of its N through BNF (>80%) regardless of variety or year. N-accumulation by cvs Babylon and Boxer increased with compost treatment in 2014/2015. Rhizobial populations were c. 10 5 -10 6 Rlv cells g −1 soil regardless of field or treatment. 157 Rlv microsymbionts grouped into two large nodAD clades; one mainly from V. faba , and the other from various legumes. All isolates nodulated, and some performed better than commercial inoculant strains. Conclusions Faba bean can provide most of its nitrogen through BNF and leave economically valuable residual N for subsequent crops. Recent legume cropping in northern Europe is not essential for effective nodulation: rhizobia may persist in a range of farmland locations. Nevertheless, there is the potential to apply elite rhizobial strains as inoculants in some soils.

Metabolic effects of high-intensity interval training and essential amino acids - Katie R. Hirsch; Casey E. Greenwalt; Hannah E. Cabre; Lacey M. Gould; Gabrielle J. Brewer; Malia N. M. Blue; Arny A. Ferrando; Kim M. Huffman; Elizabeth J. Mayer-Davis; Eric D. Ryan; Abbie E. Smith-Ryan (European Journal of Applied Physiology, 2021)

Determination of probabilities for the generation of high-discharge flows in the middle basin of Elqui River, Chile - Iván P. Vergara Dal Pont; Fernanda A. Santibañez Ossa; Diego Araneo; Francisco J. Ferrando Acuña; Stella M. Moreiras (Natural Hazards, 2018)

Vacchi's palatal organ: a widespread trait in Holocephali - B. Finucci; L. Gallus; A. Amaroli; S. Candiani; M. Rottigni; M. A. Masini; S. Ferrando (Journal of Fish Biology, 2018)
A palatal organ, possibly used for food sorting and processing, has previously been identified among the vomerine toothplates of the chimaeroid Chimaera monstrosa . In this study, the palatal organ was described in six additional species, confirming it is a widespread trait among holocephalans. It is proposed that this palatal structure, which appears to differ in shape according to each chimaeroid's degree of durophagy and is not homologous to the palatal structure described in teleosts, be hereby referred to as Vacchi's organ.

Gross morphology and histology of the olfactory organ of the Greenland shark Somniosus microcephalus - S. Ferrando; L. Gallus; L. Ghigliotti; M. Vacchi; J. Nielsen; J. S. Christiansen; E. Pisano (Polar Biology, 2016)

Taxonomic and Functional Resilience of Grasshoppers (Orthoptera, Caelifera) to Fire in South Brazilian Grasslands - C P R Ferrando; L R Podgaiski; M K M Costa; M D S Mendonça (Neotropical Entomology, 2016)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

The training-induced changes on automatism, conduction and myocardial refractoriness are not mediated by parasympathetic postganglionic neurons activity - M. Zarzoso; L. Such-Miquel; G. Parra; L. Brines-Ferrando; L. Such; F. J. Chorro; J. Guerrero; A. Guill; J. E. O’Connor; A. Alberola (European Journal of Applied Physiology, 2012)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Polymorphism of the Goat Agouti Signaling Protein Gene and Its Relationship with Coat Color in Italian and Spanish Breeds - B. Badaoui; M. D’Andrea; F. Pilla; J. Capote; A. Zidi; J. Jordana; A. Ferrando; J. V. Delgado; A. Martínez; O. Vidal; M. Amills (Biochemical Genetics, 2011)

Bioaccumulation of Heavy Metals in the Lizard Psammodromus algirus After a Tailing-Dam Collapse in Aznalcóllar (Southwest Spain) - Rocío Márquez-Ferrando; Xavier Santos; Juan M. Pleguezuelos; Diego Ontiveros (Archives of Environmental Contamination and Toxicology, 2009)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Na + /K + ATPase immunoreactivity in olfactory epithelium of small‐spotted catshark Scyliorhinus canicula (L.): possible presence of ion exchanging cells? - S. Ferrando; M. Bottaro; L. Gallus; L. Girosi; M. Vacchi; G. Tagliafierro (Journal of Fish Biology, 2006)
Na + /K + ATPase immunoreactivity in olfactory epithelium of Scyliorhinus canicula was localized in well featured light large cells. It was distributed in the basolateral membranes as reported in the literature for typical ion exchanging cells.

Melanism in the gastric mucosa of the scalloped ribbonfish from the Ligurian Sea - M. Bottaro; S. Ferrando; T. Ferrando; P. N. Psomadakis; M. Vacchi (Journal of Fish Biology, 2005)
Internal stomach melanism was observed in two scalloped ribbonfish Zu cristatus from the Ligurian Sea. The phenomenon may help prevent advertizing the presence of this species after consumption of bioluminescent prey.

Comparative Study of the Toxicity of Molinate for Freshwater Organisms - E. Sancho; M. Sanchez; M. D. Ferrando; E. Andreu-Moliner (Bulletin of Environmental Contamination and Toxicology, 2003)

Effect of an Acaricide on the Reproduction and Survival of Daphnia magna - M. J. Villarroel; E. Sancho; M. D. Ferrando; E. Andreu-Moliner (Bulletin of Environmental Contamination and Toxicology, 1999)

Sublethal Bioconcentration of Fenitrothion in the Blood and Brain of the European Eel - E. Sancho; M. D. Ferrando; A. Ten; C. Lleó; E. Andreu-Moliner (Bulletin of Environmental Contamination and Toxicology, 1998)